Kriteria Keseimbangan Dalam Perjanjian Kredit Bank Untuk Mewujudkan Keadilan Komutatif - Tiar Ramon (Fakultas Hukum Universitas Islam Indonesia, 2019)
Commutative justice is an embodiment of balance in an agreement, including a bank credit agreement as the standard. There needs to be a balance criterion proving the fulfilment of commutative justice. This study aims to determine the threshold of the balance in bank credit agreements to realize commutative justice. This research is a normative legal research, with the agreement norm system approach as the object of the research by using secondary data. The results of the study concluded that there are 3 (three) balance criteria: the absence of dominance, the harmonization of the contents of the agreement, and non-violation of the principle of justice. If these criteria are not sufficed when a lawsuit is filed, it may be used as a basis or reason according to the law, for the court to annul the agreement for violationg the principle balance.